Darboux-Bäcklund transformations and rational solutions of the painlevé IV equation - Aratyn, H.; Gomes, J. F. [UNESP]; Zimerman, A. H. [UNESP] (AIP Publishing, 2010)
Rational solutions of the Painlevé IV equation are constructed in the setting of pseudo-differential Lax formalism describing AKNS hierarchy subject to the additional non-isospectral Virasoro symmetry constraint. Convenient Wronskian representations for rational solutions are obtained by successive actions of the Darboux-Bäcklund transformations. ©2010 American Institute of Physics.
Keywords: Darboux-Bäcklund transformation; The AKNS hierarchy; The Painlevé IV equation